Structural basis for an exceptionally strong preference for asparagine residue at the S2 subsite of Stenotrophomonas maltophilia dipeptidyl peptidase 7 - Akihiro Nakamura (Nature Portfolio, 2021)
Abstract The emergence of drug-resistant bacteria has become a major problem worldwide. Bacterial dipeptidyl peptidases 7 and 11 (DPP7s and DPP11s), belonging to the family-S46 peptidases, are important enzymes for bacterial growth and are not present in mammals. Therefore, specific inhibitors for these peptidases are promising as potential antibiotics. While the molecular mechanisms underlining strict specificity at the S1 subsite of S46 peptidases have been well studied, those of relatively broad preference at the S2 subsite of these peptidases are unknown. In this study, we performed structural and biochemical analyses on DPP7 from Stenotrophomonas maltophilia (SmDPP7). SmDPP7 showed preference for the accommodation of hydrophobic amino acids at the S2 subsite in general, but as an exception, also for asparagine, a hydrophilic amino acid. Structural analyses of SmDPP7 revealed that this exceptional preference to asparagine is caused by a hydrogen bonding network at the bottom of the S2 subsite. The residues in the S2 subsite are well conserved among S46 peptidases as compared with those in the S1 subsite. We expect that our findings will contribute toward the development of a universal inhibitor of S46 peptidases.